METHODS OF PLANNING AND DISTRIBUTING TASKS IN TIME MANAGEMENT - Zhukovska , Alina (Socio-economic relations in the digital society, 2023)
One of the main components of the time management system is planning and distributing tasks. The successful completion of a task depends on many factors: how timely and relevant it is, how clearly and correctly formulated, how realistic and achievable it is, how it correlates with other tasks, whether the time required for its completion is correctly determined, and whether the deadline is optimally set. World practice has developed many methods of planning and allocating tasks. It is quite difficult to find your way in their multitude and determine which method is best suited to a given situation. The aim of the article is to develop a classification of planning and task allocation methods used in time management, to determine their advantages and disadvantages, as well as to assess their potential usefulness for different types of people and organizations. The methods of theoretical generalization (observation, comparison, abstraction, analysis and synthesis, induction and deduction), method of comparative analysis, and method of classification are applied. In the course of the research, a number of time management methods were identified, which are used for planning and distributing tasks. To facilitate the process of finding a suitable method, their classification is proposed depending on the functions they perform. According to the developed classification, methods are divided into four groups: methods of setting tasks; methods of fixing and structuring tasks; prioritization methods; principles, rules, and methods of allocating time for tasks. The author’s definition of each group of methods is proposed. The advantages and disadvantages of the analyzed methods are highlighted, as well as the situations in which these methods will be most effective are identified. The classification of methods of planning and distribution of tasks, which are used in time management, offered in the article will greatly facilitate the process of choosing the most convenient method and help potential users to fully use all their advantages.